The removal of nickel(II) ions by Cladophora crispata in a two-staged batch reactor - Özer, Ayla; Özer, Dursun (My University, 1998)
The effects of adsorption conditions on the adsorption of nickel(11) ions to inactivated Cladophora crispata, a green algae, were investigated in an agitated batch reactor. The optimum initial pH, temperature, initial metal ion concentration and microorganism concentration were found to be 5.0, 25 °C, 200 mg/L and 1.00 g/L, respectively. The Freundlich and Langmuir adsorption isotherms were developed at different initial, pH and temperature values. It was observed that the experimental data fitted both the Freundlich and Langmuir isotherm models. Under optimum adsorption conditions, the adsorption of nickel(11) ions to C.crispota was investigated in a two-stage batch reactor. For different ratios of algae concentraion (X0) to volume water containing nickel(11) (V0), the residual nickel(II) ion concentrations at the equilibrium were calculated from models developed using the isotherm constants. Then, the experimental values were compared with the theoretical values.
Nikel(II) iyonlarinin iki kademeli kesikli kapta Cladophora crispata ile giderilmesi
Keywords: Adsorption isotherms; Cladophora crispata; Equilibrium; Heavy metal adsorption; Operation line